Propuesta de documentación de un sistema de gestión de calidad basado en la Norma ISO 9001:2015 para la empresa CONSTRUNAL DE AGUAS S.A.S - Alvarez Cuevas, Faber Antonio; Ramírez Ramos, Leidy Solanyi (Universidad Antonio Nariño, 2022)
As time has passed in all companies and industries has seen a very important factor which has been determined as quality this factor has been preliminary for each of them, in which a very good benefit has been seen when implementing a management system